2017
DOI: 10.1111/cea.12992
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental exposure to peanut in the development of clinical allergy to peanut

Abstract: The prevalence of peanut allergy has increased over the years and still remains one of the most common causes of food-related anaphylaxis. The way in which peanut sensitization occurs has been explored, such as via maternal consumption in pregnancy, via breastmilk and through a disrupted skin barrier. It has previously been shown that environmental exposure to aeroallergens in household dust can be a risk factor for the development of allergic asthma. There is an increasing body of evidence that the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
14
0
1
Order By: Relevance
“…Despite the sparse amount of data on peanut allergy prevalence among Asian and other developing countries, some studies in the last 10 years have reported that the Asian population has a mixed level of sensitization toward peanut that is low in comparison to the rates reported for Western countries (see Table ). Several genetic and environmental conditions such as ethnicity, gender, genetics, and early childhood exposure to peanut are crucial factors for the increasing prevalence and severity toward peanut allergy (Foong & Brough, ; Leung, Wong, & Tang, ; Sicherer & Sampson, , ). The absence of a cure or unstandardized desensitization methodologies for food allergies may have exacerbated the issues, thus, increasing prevalence of food allergy (Tang & Mullins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sparse amount of data on peanut allergy prevalence among Asian and other developing countries, some studies in the last 10 years have reported that the Asian population has a mixed level of sensitization toward peanut that is low in comparison to the rates reported for Western countries (see Table ). Several genetic and environmental conditions such as ethnicity, gender, genetics, and early childhood exposure to peanut are crucial factors for the increasing prevalence and severity toward peanut allergy (Foong & Brough, ; Leung, Wong, & Tang, ; Sicherer & Sampson, , ). The absence of a cure or unstandardized desensitization methodologies for food allergies may have exacerbated the issues, thus, increasing prevalence of food allergy (Tang & Mullins, ).…”
Section: Introductionmentioning
confidence: 99%
“…33 We also have an improving understanding of the allergens that induce allergy reactions to foods as exemplified by Sharp and colleagues review on fish allergens. The review by Foong and Brough nicely summarizes this.…”
Section: Food Allergymentioning
confidence: 99%
“…In case-controlled studies, peanut allergy has been associated with high household peanut consumption. 1,2 Case-control studies are though very vulnerable to unrecognized confounding. So, Brough et al have looked at whether post-natal environmental peanut exposure is associated with later allergic sensitization to peanut in a population-based cohort.…”
Section: A Complicated Relationship Between Peanut Environmental Expomentioning
confidence: 99%
“…In case‐controlled studies, peanut allergy has been associated with high household peanut consumption . Case‐control studies are though very vulnerable to unrecognized confounding.…”
mentioning
confidence: 99%